Bioactive Phloroglucinyl Heterodimers: The Tautomeric and Rotameric Equlibria of Arzanol. Issue 28 (6th October 2016) - Rastrelli, Federico; Bagno, Alessandro; Appendino, Giovanni; Minassi, Alberto
Abstract : Arzanol (1 ) exemplifies a large number of heterodimeric bioactive natural products based on an alkylidene‐bridged β‐dicarbonyl‐acylphloroglucinyl structural motif. The NMR spectra of these compounds are complicated by tautomeric and rotational equilibria that, despite growing synthetic and biomedical interest in the area, have not been systematically investigated. By combining information from NMR spectroscopy and DFT calculations, we have comparatively characterized the solution structures and conformations of the anti‐inflammatory agent arzanol (1 ), its inactive monomethyl derivative4, and its corresponding homodimers [helipyrone (5 ) and demethylmallotojaponin C (6 )]. The results highlight the relevance of a network of intramolecular hydrogen bonds for the tautomeric and rotameric equilibria of these compounds, with arzanol (1 ) existing in two almost equally populated rotameric forms of a 2‐pyrone tautomer, and its phloroglucinyl homodimer6 in four major forms. Conversely, the monomethyl derivative4 of arzanol and its dipyrone homodimer5 exist in essentially a single solution form. Interestingly, this conformational bias was associated with a marked decrease of bioactivity. Abstract : Combined NMR spectroscopy and DFT calculations elucidate the solution structures and conformations of arzanol, the major anti‐inflammatory constituent of everlasting ( Helichrysum italicum ). The image of Helichrysum Italicum was provided courtesy of Erbario dell'Università di Padova.